Biomimetic Total Syntheses of (−)‐Leucoridines A and C through the Dimerization of (−)‐Dihydrovalparicine. (10th September 2015) - Kokkonda, Praveen; Brown, Keaon R.; Seguin, Trevor J.; Wheeler, Steven E.; Vaddypally, Shivaiah; Zdilla, Michael J.; Andrade, Rodrigo B.
Abstract Concise biomimetic syntheses of the Strychnos‐Strychnos‐type bis‐indole alkaloids (−)‐leucoridine A (1) and C (2) were accomplished through the biomimetic dimerization of (−)‐dihydrovalparicine (3). En route to 3, the known alkaloids (+)‐geissoschizoline (8) and (−)‐dehydrogeissoschizoline (10) were also prepared. DFT calculations were employed to elucidate the mechanism, which favors a stepwise aza‐Michael/spirocyclization sequence over the alternate hetero‐Diels–Alder cycloaddition reaction.